Purchase Intention Model For Rural Tourism - Hikmatul Aliyah; Ahmad Mustofa (LPPM ITB AAS INDONESIA (d.h STIE AAS Surakarta), 2021)
The purpose of this paper is to examine and analyze the effect of green product, green place, environmental knowledge on purchase intention. Population this research is all visitors to Kerang Mas Beach. The total sample of this study was 112 people. Hypothesis testing and analysis using Structural Equation Modeling (SEM). The results of this study indicate that the effect of green place on purchase intention is not supported. However, the effect of green products on environmental knowledge, the effect of green place on environmental knowledge, the effect of environmental knowledge on purchase intention, and the effect of green products on purchase intention. This research will help rural tourism management to develop new marketing strategies to increase purchase intention, and also, will help researchers with further empirical investigations. Keywords: Green Product, Green Place, Environmental Knowledge, Purchase Intention